Endoplasmic Reticulum Stress/Ca2+-Calmodulin-Dependent Protein Kinase/Signal Transducer and Activator of Transcription 3 Pathway Plays a Role in the Regulation of Cellular Zinc Deficiency in Myocardial Ischemia/Reperfusion Injury - Zhao, Huanhuan; Liu, Dan; Yan, Qiumei; Bian, Xiyun; Yu, Jing; Wang, Jingjing; Cheng, Xinxin; Xu, Zhelong (Frontiers in Physiology, 2022)
Zinc homeostasis has been known to play a role in myocardial ischemia/reperfusion (I/R) injury, but the precise molecular mechanisms regulating the expression of ZIP transporters during reperfusion are still unclear. The aim of this study was to determine whether ER Stress/CaMKII/STAT3 pathway plays a role in the regulation of cellular zinc homeostasis. Zinc deficiency increased mRNA and protein expressions of the ER stress relevant markers Chop and Bip, and STAT3 phosphorylation in H9c2 or HL-1 cells, an effect that was abolished by ZnCl2. ER calcium concentration ([Ca2+]ER) was decreased and cytosolic calcium concentration ([Ca2+]I) was increased at the condition of normoxia or ischemia/reperfusion, indicating that zinc deficiency triggers ER stress and Ca2+ leak. Further studies showed that upregulation of STAT3 phosphorylation was reversed by Ca2+ chelator, indicating that intracellular Ca2+ is important for zinc deficiency-induced STAT3 activation. In support, zinc deficiency enhanced ryanodine receptors (RyR), a channel in the ER that mediate Ca2+ release, and Ca2+-calmodulin-dependent protein kinase (CaMKII) phosphorylation, implying that zinc deficiency provoked Ca2+ leak from ER via RyR and p-CaMKII is involved in STAT3 activation. Moreover, inhibition of STAT3 activation blocked zinc deficiency induced ZIP9 expression, and resulted in increased Zn2+ loss in cardiomyocytes, further confirming that STAT3 activation during reperfusion promotes the expression of ZIP9 zinc transporter to correct the imbalance in zinc homeostasis. In addition, suppressed STAT3 activation aggravated reperfusion injury. These data suggest that the ER Stress/CaMKII/STAT3 axis may be an endogenous protective mechanism, which increases the resistance of the heart to I/R.